The effect of an urban park on the microclimate in its vicinity: a case study for Antwerp, Belgium. (6th December 2017) - Toparlar, Y.; Blocken, B.; Maiheu, B.; van Heijst, G. J. F.
Abstract : The cooling effect from an urban park located in Antwerp, Belgium is analysed with computational fluid dynamics simulations. The analysis is based on three cases: (1) base case with the park, (2) a case where the park is replaced by a square and (3) a case where the park is replaced by representative buildings. According to the results, the cooling effect reaches a maximum of 3.4 °C in the park vicinity and remains noticeable to a maximum range of 498 m in line with the prevailing wind direction. ABSTRACT: An urban park can exhibit a cooling effect not only in the park itself, but also in its wake with respect to the prevailing wind. This study investigates the cooling potential of an urban park in Antwerp, Belgium focusing on two parameters: (1) intensity of the cooling effect, indicating the maximum reduction in air temperature and (2) range of the cooling effect, indicating the maximum horizontal distance where a minimum of 0.1 °C cooling effect is present. Computational fluid dynamics (CFD) simulations are performed using the three‐dimensional unsteady Reynolds‐averaged Navier–Stokes equations. Coupled simulations of wind flow and heat transfer consider all the conductive, convective and radiative heat transfer processes but not the long‐wave radiation heat exchange between buildings, trees and ground. The vegetation model used in this study is evaluated with experimental data from an earlier study. Moreover, the simulated air temperatures inside the Antwerp city center are compared with available measurement data. Following the fairly‐good predictions from CFD simulations, results from the following cases are compared: (1) base case with the park, (2) a case with an open square instead of the park, and (3) a case with representative buildings instead of the park. The results indicate a maximum daytime intensity and range of the cooling effect of 3.4 °C and 498 m at 1500 LST (UTC + 2, Central European Summer Time). Further analysis shows that the cooling effect is more profound closer to the ground. Apart from the daytime cooling effect, the park investigated has the potential to lower wind velocities, resulting in increased air temperatures during the night‐time (at 0000 LST) by 0.9 °C, although this number might be slightly different given the neglect of long‐wave radiation heat exchange between buildings, trees and ground.